Ectoparasites of Birds from a Rice Field in Samarahan Division, Sarawak - Nur Athirah, Asrif; Karim, Nurqamareena; Chong, Yee Ling (Universiti Malaysia Sarawak (UNIMAS), 2018)
Birds are easily infested with ectoparasites due to their fitness, foraging behaviour, nesting cavities, micro- and macro-habitats. However, the status of ectoparasite infestation on birds in Sarawak is widely unknown. Rice field provides food resources to a variety of birds. This study was conducted to determine the species composition of ectoparasites from birds in a rice field at Kuap Village, Samarahan, Sarawak. A total of 69 birds consists of five species were caught from the rice field and the most common bird species found was the Chestnut Munia (Lonchura atricapilla). From these, 55 were found infested with ectoparasites with the infestation prevalence of 79.71%. A total of 2,513 ectoparasites from eight species were recovered from this study which comprised of six species of mites, one species of soft tick, and one species from the class Insecta. The most dominant ectoparasite species was mite namely, Nanopterodectes sp. with a total of 1,626 individuals. This baseline data on the ectoparasite composition and infestation of birds is important as some of the ectoparasites have the potential in transmitting zoonotic diseases to the farmers working at the rice fields in this region.